An Unusual Atrial Septal Defect Producing Symptoms in a Young Lady - Alam, Md. Mashiul; Al-Amin, Md. (International Journal of Innovative Research in Medical Science, 2020)
Atrial septal defect is the most common congenital heart disease among adult population. Secundum variety of atrial septal defect comprises most frequently encountered atrial septal anomaly which presents during late age. Primum atrial septal defect usually associated with atrio-ventricular cushion defect among patients with Down syndrome. Small number of patients may present with fenestrated atrial septal defect. We have presented case of a woman who is young and symptomatic due to atrial septal defect comprising both secundum and primum type.